2013
DOI: 10.1111/jop.12141
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral DNAHPV and genital DNAHPV

Abstract: The prevalence of HPV in the oral cavity was significantly higher in women who had genital HPV (P < 0.0001). Oral sex, alcohol, and tobacco consumption were not associated with the oral HPV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
13
0
2
Order By: Relevance
“…Several studies have found that sexual behavior (i.e., marital status, number of sex partners, oral sex, and anal sex), smoking, and alcohol drinking are significant risk factors for oral HPV infection [10-13, 20, 23, 30, 31, 33]. Therefore, we performed a meta-analysis to investigate the association between overall oral HPV infection and outcome, as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found that sexual behavior (i.e., marital status, number of sex partners, oral sex, and anal sex), smoking, and alcohol drinking are significant risk factors for oral HPV infection [10-13, 20, 23, 30, 31, 33]. Therefore, we performed a meta-analysis to investigate the association between overall oral HPV infection and outcome, as described above.…”
Section: Resultsmentioning
confidence: 99%
“…Lira (2010) 25 Mean of 65 y ------49/26 Oliveira (2008) 26 Mean of 59 y 81.6% ---73/14 Simonato (2008) 27 79.3% under 60 y 89.7% 62.1% 27/2 Soares (2008) 28 Mean of 65 y ---------Oliveira (2009) 29 59% over 60 y ------57/31 Pereira (2011) 30 Mean of 63 y ------19/8 Spindula-Filho (2011) 31 55.3% over 65 y 72.3% 61.7% 34/13 Cordeiro-Silva (2012) 32 44.5% over 58 y 80.0% 68.9% 35/10 Kaminagakura (2012) 33 Mean of 51 y 84.0% 62.0% 81/33 Marques-Silva (2012) 34 33 38 Mean of 45 y ------21/43 Ribeiro (2014) 39 Mean of 32 y 27.4% ---31/31 Vidotti (2014) 40 42 Mean of 29 y ------30/0 Peixoto (2011) 43 Mean of 37 70 3 (4.3%) ---------Sacramento (2006) 6 50 7 (14.0%) 1 (2.0%) 1 (2.0%) 2 (4.0%) Silva (2007) 16 10 1 (10.0%) ---------Esquenazi (2010) 7 100 0 (0.0%) ---------Horewicz (2010) 8 104 0 (0.0%) 0 (0.0%) ------Araujo (2011) 45 16 1 (6.2%) 0 (0.0%) 0 (0.0%) 0 (0.0%) Betiol (2012) 13 22 16 16 (100.0%) ---------Mazon (2011) 17 18 6 (33.0%) 0 (0.0%) 0 (0.0%) 0 (0.0%) Fregonezi (2012) 23 Oral/oropharyngeal HPV infection in patients with oral or oropharyngeal SCC Miguel (1998) 24 28 4 (14.3%) ---------Soares (2002) 18 10 0 (0.0%) ---------Soares (2003) 19 27 13 (48.1%) ------10 (37.0%) Fregonesi (2003) 20 17 6 (35.3%) ------5 (29.0%) Cortezzi (2004) 15 16 4 (25.0%) 4 (25.0%) ------Silva (2007) 16 50 37 (74.0%) ---------Soares (2007) 27 29 5 (17.2%) --------...…”
Section: Comparative Studies (Benign Lesions Versus Scc Patients)mentioning
confidence: 98%
“…A legújabb, 2014-ben megjelent tanulmányok Brazíliá-ban, illetve Németországban [10][11][12] 65, illetve 129 nő-beteg mintáiban vizsgálták az orális és genitális HPV megoszlását az orális és genitális nyálkahártyákon. A szerzők eltérő következtetésre jutottak.…”
Section: Megbeszélésunclassified
“…Marques és mtsai [10] egyértelmű összefüggést találtak az orális szex és az alkohol, valamint a dohányzási szokások között. Ezekkel az eredményekkel szemben Vidotti és mtsai [12] nem találtak olyan specifi kus faktort, amely prediszponáló té-nyező lehetne az orális HPV előfordulására. Utóbbi vizsgálók alacsony orális előfordulási arányt állapítottak meg, akárcsak mi a saját tanulmányunkban.…”
Section: Megbeszélésunclassified